The Effect of Quantum Teaching Learning Model on the Physics Learning Outcomes of Class X SMK Negeri 3 Lubuklinggau - Wita Romita Ayu; Tri Ariani; Wahyu Arini (Kasuari: Physics Education Journal (KPEJ), 2019)
The purpose of this study was to determine "The Effect of Quantum Teaching Learning Model on Physics Learning Outcomes of Class X Students of SMK Negeri 3 Lubuklinggau in 2018/2019 Academic Year". This research is motivated by the low student physics learning outcomes. The purpose of this study was to determine the effect of the pre-test post-test group design model. The population in this study were all grade X class of SMK Negeri 3 Lubuklinggau in the 2018/2019 academic year. Two classes were chosen by random sampling, namely class X TKJ II as an experimental class and class X TKJ I as a control class. Data collection techniques using test techniques. Student test score data were analyzed using the t test. Based on the results of post-test data analysis of the experimental class and the control class with a 0.5% confidence level obtained tcount = 6.9 and ttable= 2.00 because tcount>ttable, means the average score of the experimental class is greater than the control class, then it was concluded that there was a significant effect of the Quantum Teaching learning model on physics learning outcomes of class X students of SMK Negeri 3 Lubuklinggau in the 2018/2019 academic year.